(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
This article explores the importance of studying history, emphasizing how understanding the past can shape the future. By analyzing past events, societies, and innovations, the article highlights how history helps us avoid mistakes, learn from successes, and understand the interconnectedness of global events. A global perspective on history is also emphasized, as it fosters empathy and a deeper understanding of diverse cultures.